Meningkatkan hasil belajar matematika siswa melalui model pembelajaran kooperatif tipe team assisted individulaization berbantuan handout - Serli Marliani; Nurul Astuty Yensy; Effie Efrida Muchlis; Celsy Yulia Sari (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2023)
The background of this research is the low learning outcomes of students' mathematics because the tendency of students to read and understand the material in printed books is still low and teachers still apply one-way learning interactions so that students tend to be passive. Thus, the purpose of this research is to improve students' mathematics learning outcomes by applying the Team Assisted Individualization type cooperative learning model with the help of Handouts. The type of research that will be applied is Classroom Action Research (CAR) which consists of planning, implementation, observation, and reflection. This research was conducted in 3 cycles. Data was collected by means of learning outcomes tests. The subject and place of the research was SMA Negeri 03 Bengkulu Tengah in class XI IPA K with 23 students consisting of 18 girls and 5 boys. From the results of the research and discussion, it was concluded that learning outcomes increased with the practice questions made in a structured manner and with the correction process students were able to understand the material. The percentage of complete learning outcomes classically from cycle 1 to cycle 3 is 65.21% in the first cycle, 78.260% in the second cycle and 86.04% in the third cycle, which means that in each cycle learning outcomes increase.